Post-Vasectomy Semen Analysis: Optimizing Laboratory Procedures and Test Interpretation through a Clinical Audit and Global Survey of Practices - Ashok Agarwal; Sajal Gupta; Rakesh K. Sharma; Renata Finell; Shinnosuke Kuroda; Sarah C. Vij; Florence Boitrelle; Parviz Kavoussi; Amarnath Rambhata; Ramadan Saleh; Eric Chung; Taymour Mostafa; et al. (The World Journal of Men's Health, 2022)
Purpose:Purpose: The success of vasectomy is determined by the outcome of a post-vasectomy semen analysis (PVSA). This article describes a step-by-step procedure to perform PVSA accurately, report data from patients who underwent post vasectomy se-men analysis between 2015 and 2021 experience, along with results from an international online survey on clinical practice. Materials and Methods:Materials and Methods: We present a detailed step-by-step protocol for performing and interpretating PVSA testing, along with recommendations for proficiency testing, competency assessment for performing PVSA, and clinical and laboratory sce-narios. Moreover, we conducted an analysis of 1,114 PVSA performed at the Cleveland Clinic’s Andrology Laboratory and an online survey to understand clinician responses to the PVSA results in various countries. Results:Results: Results from our clinical experience showed that 92.1% of patients passed PVSA, with 7.9% being further tested. A total of 78 experts from 19 countries participated in the survey, and the majority reported to use time from vasectomy rather than the number of ejaculations as criterion to request PVSA. A high percentage of responders reported permitting unpro-tected intercourse only if PVSA samples show azoospermia while, in the presence of few non-motile sperm, the majority of responders suggested using alternative contraception, followed by another PVSA. In the presence of motile sperm, the major-ity of participants asked for further PVSA testing. Repeat vasectomy was mainly recommended if motile sperm were observed after multiple PVSA’s. A large percentage reported to recommend a second PVSA due to the possibility of legal actions. Conclusions:Conclusions: Our results highlighted varying clinical practices around the globe, with controversy over the significance of non-motile sperm in the PVSA sample. Our data suggest that less stringent AUA guidelines would help improve test compli-ance. A large longitudinal multi-center study would clarify various doubts related to timing and interpretation of PVSA and would also help us to understand, and perhaps predict, recanalization and the potential for future failure of a vasectomy.